TEACHERS' EFFORTS IN FOSTERING STUDENTS MORALS AT MADRASAH TSANAWIYAH SUBULUSSALAM WEST PASAMAN REGENCY - Elfa Era, Wedia; Habibullah; Aiman Abu Bakar, Meor Afif; Alwizra (Mandeh : Jurnal Pendidikan Islam, 2026)
This research is entitled "Teachers' Efforts in Developing Students' Morals at Madrasah Tsanawiyah Subulussalam, West Pasaman Regency." The background of this study lies in the importance of teachers' roles in shaping students' morals amid the challenges of globalization, the influence of social media, and the decline of discipline and manners among adolescents. The purpose of this research is to identify the efforts made by teachers in fostering students' morals, as well as the supporting and inhibiting factors they encounter. The study employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving teachers, the head of the madrasah, and students. The data were analyzed through reduction, data presentation, and drawing conclusions. The findings reveal that teachers' efforts in fostering students' morals are carried out through role modeling (uswah hasanah), habituation of religious and disciplined behavior, the integration of religious values ​​in learning, and providing regular advice. Supporting factors include the religious school environment, religious programs, and parental support. Meanwhile, inhibiting factors come from the negative influence of social media, peer environment, and the low motivation of some students. The study concludes that the success of moral development requires synergy among teachers, families, and the school environment. Teachers' efforts must be carried out consistently, sustainably, and integrated into all aspects of madrasa education.